2017
DOI: 10.1128/jcm.00417-17
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Robust Identification of the Agents of Black-Grain Mycetoma by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Eumycetoma, a chronic fungal infection endemic in India, Indonesia, and parts of Africa and South and Central America, follows traumatic implantation of saprophytic fungi and frequently requires radical surgery or amputation in the absence of appropriate treatment. Fungal species that can cause black-grain mycetomas include Madurella spp., Falciformispora spp., Trematosphaeria grisea, Nigrograna mackinnonii, Pseudochaetosphaeronema larense, Medicopsis romeroi, and Emarellia spp. Rhytidhysteron rufulum and Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Fraser et al [11] in 2017 developed a MALDI-TOF MS library that successfully identified 13 M. mycetomatis and 2 M. fahalii. This method, however, similar to Sanger sequencing, requires a costly purchase and maintenance that prevents their implementation in lowresource countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fraser et al [11] in 2017 developed a MALDI-TOF MS library that successfully identified 13 M. mycetomatis and 2 M. fahalii. This method, however, similar to Sanger sequencing, requires a costly purchase and maintenance that prevents their implementation in lowresource countries.…”
Section: Discussionmentioning
confidence: 99%
“…Both positive and negative biopsies were cultured on Sabouraud's Glucose Agar (SGA) and the identity of the isolates was established by ITS sequencing. These clinical samples were retrospectively collected and in a context of a blind test set they were assigned with numerical code numbers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The assessor of the qPCR assay was not aware of the identity of DNA samples (for both DNA samples derived from pure cultures and those obtained from clinical samples).…”
Section: Clinical Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was used previously, mostly for yeasts, but more recently it has been also adapted for identifying molds. A recent study by Fraser et al also demonstrated the usefulness of this technique for coelomycetes that produce black grain mycetoma.…”
Section: Laboratory Identificationmentioning
confidence: 96%
“…Recently, the use of matrix‐assisted laser desorption ionization–time of flight (MALDI‐TOF) mass spectrometry for identifying microorganisms in the clinical laboratory has rapidly become important . This technique was used previously, mostly for yeasts, but more recently it has been also adapted for identifying molds.…”
Section: Laboratory Identificationmentioning
confidence: 99%